Analysis of Validation Development Learning Model Attainment Concept to Improve Critical Thinking Skills and Student Learning Outcomes - Kartini Kartini; Aris Doyan; Kosim Kosim; Susilawati Susilawati; Baiq Uswatul Khasanah; Syamsul Hakim; Lalu Muliyadi (Postgraduate, University of Mataram, 2019)
Abstract: This study aims to produce a product in the form of a science learning model for the acquisition of motion material concepts in valid objects, with the development path using a 4D model consisting of 4 stages of development namely define, design, develop, and disseminate. Learning tools developed are syllabus, Lesson Plain, SAS and tests of critical thinking skills and student learning outcomes. However, at this writing focused on the process of validation testing through validation tests on the development of devices made. The final result of this study is to produce valid learning development products. Keywords: Learning Devices, Validation